2020
DOI: 10.1590/0037-8682-0477-2020
|View full text |Cite
|
Sign up to set email alerts
|

Current evidence of neurological features, diagnosis, and neuropathogenesis associated with COVID-19

Abstract: Recent reports indicate that besides respiratory and systemic symptoms among coronavirus disease (COVID-19) patients, the disease has a wide spectrum of neurological manifestations (encephalitis, meningitis, myelitis, acute disseminated encephalomyelitis, metabolic and acute hemorrhagic necrotizing encephalopathy, cerebrovascular diseases, Guillain-Barré syndrome, polyneuritis cranialis, dysautonomia, and myopathies). The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can spread from the respirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 41 publications
0
31
0
4
Order By: Relevance
“…According to previous literatures, SARS-CoV-2 infection can cause complications via direct invasion and immune disturbance through hematogenous or transsynaptic propagation (Figure 2) (Haddadi and Asadian, 2020;Puccioni-Sohler et al, 2020). SARS-CoV-2 is regarded as neurotropic virus.…”
Section: Mechanism Of Sars-cov-2 Infectionmentioning
confidence: 96%
See 3 more Smart Citations
“…According to previous literatures, SARS-CoV-2 infection can cause complications via direct invasion and immune disturbance through hematogenous or transsynaptic propagation (Figure 2) (Haddadi and Asadian, 2020;Puccioni-Sohler et al, 2020). SARS-CoV-2 is regarded as neurotropic virus.…”
Section: Mechanism Of Sars-cov-2 Infectionmentioning
confidence: 96%
“…Neurological manifestations could occur in the central nervous system (CNS), peripheral nervous system (PNS), and relative skeletal muscles (Kutlubaev, 2020 ; Mao et al, 2020 ; Puccioni-Sohler et al, 2020 ). A systematic review about 290 patients revealed that 91% of patients with neurological discomfort present with CNS symptoms, while only PNS symptoms account for 9% (Ibrahim, 2020 ).…”
Section: Neurological Complications Of Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…Intrathecal SARS-CoV-2 IgG and specific IgM in CSF have been found in RT-PCR assay-negative COVID-19 cases. These markers may be promising for the diagnosis of COVID-19 in cases with CNS symptoms ( 23 ). Calculation of the IgG antibody index (AI) is based on Reiber's method ( 24 ).…”
Section: Discussionmentioning
confidence: 99%